Evaluar el selle apical en dientes con formación apical incompleta a partir de la inducción con fibrina rica en plaquetas: Un reporte de caso - Ortiz Rodríguez, Sandy Julieth; Durán Botia, Lineth Piedad (Universidad Antonio Nariño, 2022)
Pulp necrosis in immature teeth is a pathology with high frequency in children and adolescents, generally associated with trauma or a dental caries that compromises the functionality of the tooth and its longevity in the mouth. The commonly managed protocol is conventional root canal treatment. Recently, regenerative therapies have been introduced that restore vitality but with high-cost materials. Platelet-rich fibrin has shown regenerative potential in other areas of dentistry. It is possible that PRF could help promote revitalization of teeth with these types of cases.